Kant e as analogias musicais - Rancan de Azevedo Marques, Ubirajara [UNESP] (Universidad Complutense de Madrid (UCM), 2011)
Besides a philosophical glossary, Kant handles many other linguistic repertoires; among them, for instance, the musical ones. The present study, by considering the kantian musical lexicon, is not intended to promote the music in the realm of critical philosophy from a aesthetic point of view, but to recognize and to examine in a preliminary manner an argumentative resource used by the philosopher, namely, the musical analogy.
Kant and the musical analogies
Keywords: Analogy; Harmony; Kant; Melody; Music